Economic Survey on a Community of Prosumers and Distributed Generations - Abrishambaf, Omid (2021)
The use of demand response programs and distributed renewable energy resources play an important role in nowadays electricity markets. Most of the demand response programs are performed for large-scale resources. This is a barrier for the small and medium scale consumers, producers, and prosumers in order to participate in the electricity market negotiations. To overcome this barrier, a third-party entity, such as community or an aggregator, should play a role an intermediate player between the end-users and network operators. However, before the implementation of the business models, they should be well surveyed in term of economic and financial profits in order to prevent future problems. This paper proposes an economic survey on a community of the consumers and distributed generations, considering different pricing schemes. The community consists of residential, commercial, and industrial consumers as well as photovoltaic and wind turbines. In this survey, the annual costs of this community are investigated considering the current pricing schemes in two countries of Portugal and Germany.